Effects of Antihypertensive Drugs Use on Risk and Prognosis of Colorectal Cancer: A Meta-Analysis of 37 Observational Studies - Deng, Yujiao; Xie, Yuxiu; Wang, Meng; Xu, Peng; Wei, Bajin; Li, Na; Wu, Ying; Yang, Si; Zhou, Linghui; Hao, Qian; Lyu, Lijuan; Zhang, Dai; et al. (Frontiers in Pharmacology, 2022)
Background: Antihypertensive drugs might play a key role in the risk and poor prognosis of colorectal cancer. However, current epidemiologic evidence remains inconsistent. The aim of this study is to quantify the association between antihypertensive drugs and colorectal cancer. Methods: To identify available studies, we systematically searched electronic databases: PubMed, Web of Science, Embase, Cochrane Library. The risk estimates and their corresponding 95% confidence intervals (CIs) were collected and analyzed by using random-effects models. Heterogeneity test and sensitivity analysis were also performed. Results: Overall, 37 observational studies were included in this analysis (26 studies with cohort design, three studies with nested case-control design, and 8 studies with case-control design). Antihypertensive drugs did not present a significant effect on the risk or overall survival of patients with colorectal cancer (Risk ratio (RR) =1.00, 95% CI: 0.95-1.04; Hazard ratio (HR) = 0.93, 95% CI: 0.84-1.02). In the subgroup analysis, diuretics use was significantly associated with a worse overall survival of patients with colorectal cancer (HR=1.27; 95% CI: 1.14-1.40).However, use of angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers was associated with improved progression-free survival of patients who suffered from colorectal cancer (HR = 0.83; 95% CI: 0.72-0.95). Conclusions: Antihypertensive drug usage did not influence the risk and overall survival of patients with colorectal cancer in general. Further investigation reminded us that diuretics use might reduce the overall survival time in colorectal cancer patients, whereas those who took Angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers had a longer progression-free survival.